PENGEMBANGAN POTENSI EKOWISATA DI DESA LIANG NDARA KABUPATEN MANGGARAI BARAT - Ada, Aurilia Hansni Yanita; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA, 2017)
Liang Ndara Village is one of the villages in West Manggarai Regency, which has ecotourism potential. Yet, based on the observation, the development of ecotourism potential is not maximize yet, so base on the case the observation was doing in order to know the potentials and the attraction of ecotourism, knowing the ecotourism practice and its similarity with ecotourism principles and to decide what action going to take in develop the ecotourism potential in Liang Ndara village with the research method of qualitative. The data collecting by observation, deeper interview, library study and the informant technique which is used is purposive sampling, that is the researcher deciding the informant base on the research purpose. The output of the research shows that the potential and the attraction of the ecotourism in Liang Ndara village is Mbeliling Mountain Liang Kantor Waterfall, Cunca rami Waterfall, Liang Niki cave, Puncak Melo, attraction and culture, Compang kafir stone, logam Talang, weaving, Arak or local wine filtration and ricefield culturation. The practice of ecotourism in Liang Ndara village is not the same as the principles of ecotourism. There are eight criteria of ecotourism, which is not fulfilled yet. The ideal effort of ecotourism development is by fulfilling some criteria that is not fulfilled yet.
Keywords: ecotourism, potential, development